Efektivitas Penggunaan Buku Cerita Rakyat Lokal dalam Meningkatkan Kemampuan Literasi Anak Kelompok B - Salsabilla, Tiara; Aryani, Nini; Wilyanita, Nopa (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
Early literacy skills serve as a crucial foundation for cognitive and language development. This study aims to describe the improvement of literacy skills in children aged 5-6 years through the use of Riau folklore storybooks. The research method employed was Classroom Action Research (CAR) conducted in two cycles. The subjects consisted of 11 children (7 boys and 4 girls) in Group B of TK Mustika Bunda Pekanbaru. Data were collected through observation and documentation, then analyzed using descriptive comparative techniques. The results showed a significant increase in children's literacy skills. During the pre-cycle stage, the majority of children (63.6%) were in the "Starting to Develop" (MB) category. After the intervention in Cycle I, 45.4% of children reached the "Developed as Expected" (BSH) category. The most significant improvement occurred in Cycle II, where 81.8% of children achieved the "Very Well Developed" (BSB) category. These findings conclude that integrating local wisdom through Riau folklore storybooks is effective in stimulating early childhood literacy skills in an interactive and contextual manner.